Eye and Head Movement Recordings Using Smartphones for Telemedicine Applications: Measurements of Accuracy and Precision - Parker, T. Maxwell; Badihian, Shervin; Hassoon, Ahmed; Saber Tehrani, Ali S.; Farrell, Nathan; Newman-Toker, David E.; Otero-Millan, Jorge (Frontiers in Neurology, 2022)
Objective: Smartphones have shown promise in the assessment of neuro-ophthalmologic and vestibular disorders. We have shown that the head impulse test results recorded using our application are comparable with measurements from clinical video-oculography goggles. The smartphone uses ARKit’s capability to acquire eye and head movement position without the need of performing a calibration as in most eye tracking devices. Here we measure the accuracy and precision of the eye and head position recorded using our application. Methods: We enrolled healthy volunteers and asked them to direct their eyes, their head, or both to targets on a wall at known eccentricities while recording their head and eye movements with our smartphone application. We measured the accuracy as the error between the eye or head movement measurement and the location of each target and the precision as the standard deviation of the eye or head position for each of the target positions. Results: The accuracy of head recordings (15% error) was overall better than the accuracy of eye recordings (23% error). We also found that the accuracy for horizontal eye movements (17% error) was better than for vertical (27% error). Precision was also better for head movement (0.8 deg) recordings than eye movement recordings (1.3 deg) and variability tended to increase with eccentricity.